Gender specific variation in risk factors of gallstone disease among adult patients - Dhamnetiya, Deepak; Goel, Manish K.; Dhiman, Balraj; Pathania, Om P. (International Surgery Journal, 2019)
Background: Gallstone disease (GSD) is a common gastrointestinal disease diagnosed in patients presented with abdominal pain. The present study was aimed to find the association between demographic, personal, behavioural and dietary factors and GSD by gender among adult population for suggesting specific gender wise intervention to control GSD. Methods: Case-control study was conducted in 120 cases and same number of controls. Data was collected on a self-designed pretested “interview schedule”. To measure the strength of association OR was calculated by matched pair analysis using McNemar’s test. Results: Among 120 study subjects, 83 cases were females and 37 were males. Strength of association was found to be significantly higher for family h/o GSD in females (OR=8), physical inactivity (OR=8), waist-hip ratio (OR=4.2), calorie intake more than recommended dietary allowance (RDA) (OR=2.09), and diabetes (OR=4) as compare to males OR=3, OR=2.8, OR=2.5, OR=1.43, OR=2.33 respectively. Conclusions: Family h/o GSD, physical inactivity, high waist-hip ratio, calorie and fat intake more than RDA, protein intake less than RDA, hypertension and diabetes were found to be potential risk factors for the development of GSD in females. Consumption of smokeless tobacco, physical inactivity, non-vegetarian diet and intake of fats more than RDA were risk factors for GSD in males.